Co-prescribing of opioids and benzodiazepines/Z-drugs associated with all-cause mortality—A population-based longitudinal study in primary care with weak opioids most commonly prescribed - Linnet, Kristjan; Thorsteinsdottir, Heidrun Sjofn; Sigurdsson, Johann Agust; Sigurdsson, Emil Larus; Gudmundsson, Larus Steinthor (Frontiers in Pharmacology, 2022)
Introduction: The risk of mortality associated with the co-prescribing of benzodiazepines and opioids has been explored in a number of papers mainly focusing on strong opioids. The mortality risk associated with the use of weak opioids has not been dealt with to a similar extent. Objective: To assess the mortality risk in primary care patients with consistent three-year co-prescribing of benzodiazepine/Z-drugs (benzodiazepine receptor modulators) and mainly weak opioids. Methods: Of 221,804 patients contacting the primary healthcare centres, 124,436 were selected for further analysis, 88,832 participants fulfilled the inclusion criteria, aged 10-69 years, divided into four groups with neither any use of benzodiazepines/Z-drugs nor opioids as Group 1, three years’ use of opioids and no/minimal benzodiazepines/Z-drugs as Group 2, with benzodiazepines/Z-drugs and no/minimal opioids as Group 3, and finally both benzodiazepines/Z-drugs and opioids as Group 4. Results: Hazards ratios were calculated with the no-drug group as a reference, using Cox proportional hazards regression model adjusted for age, sex, number of chronic conditions and cancer patients excluded (n=87,314). Hazards ratios for mortality increased both in Group 3 where it was 2.66 (95% CI 2.25-3.09) and in Group 4 where it was 5.12 (95% CI 4.25-6.17), with increased dose and higher number of chronic conditions. Conclusions: Mortality increased in a dose-dependent manner in patients co-prescribed benzodiazepines/Z-drugs and either codeine or tramadol or both. An association between the number of chronic conditions and a rise in mortality was found. Long-term use of these drugs should preferably be avoided. Non-pharmacological therapy should be seriously considered instead of long-term use of benzodiazepines/Z-drugs, and deprescribing implemented for chronic users of these drugs.